2018
DOI: 10.1177/0333102418788336
|View full text |Cite
|
Sign up to set email alerts
|

Gain of function of sporadic/familial hemiplegic migraine-causing SCN1A mutations: Use of an optimized cDNA

Abstract: Introduction Familial hemiplegic migraine 3 is an autosomal dominant headache disorder associated with aura and transient hemiparesis, caused by mutations of the neuronal voltage-gated sodium channel Nav1.1. While a gain-of function phenotype is generally assumed to underlie familial hemiplegic migraine, this has not been fully explored. Indeed, a major obstacle in studying in vitro neuronal sodium channels is the difficulty in propagating and mutagenizing expression plasmids containing their cDNAs. The aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 41 publications
6
33
0
Order By: Relevance
“…With wholecell patch-clamp recordings of Na + currents in cell lines, we first confirmed that also in our conditions Hm1a at low concentration (10 nM) selectively targets NaV1.1 over the two other NaV isoforms expressed in the adult cortex, NaV1.2 and NaV1.6 ( Supplementary Fig.S1). Importantly, Hm1a induced a 12-fold increase of persistent current, effect that is comparable to that previously observed with FHM3 mutations Bertelli et al, 2019;Cestele et al, 2008;Cestele et al, 2013b;Dhifallah et al, 2018), making it a good pharmacological tool for modeling the effect of these mutations.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…With wholecell patch-clamp recordings of Na + currents in cell lines, we first confirmed that also in our conditions Hm1a at low concentration (10 nM) selectively targets NaV1.1 over the two other NaV isoforms expressed in the adult cortex, NaV1.2 and NaV1.6 ( Supplementary Fig.S1). Importantly, Hm1a induced a 12-fold increase of persistent current, effect that is comparable to that previously observed with FHM3 mutations Bertelli et al, 2019;Cestele et al, 2008;Cestele et al, 2013b;Dhifallah et al, 2018), making it a good pharmacological tool for modeling the effect of these mutations.…”
Section: Resultssupporting
confidence: 80%
“…CSD was induced in the neocortex both by optogenetic activation of GABAergic neurons and by activation of NaV1.1 with the specific toxin Hm1a (Osteen et al, 2016). This is consistent with the key role of NaV1.1 in GABAergic neurons' excitability and with the effect of FHM3 mutations, which cause gain of function of NaV1.1 and can induce an increase of the persistent Na + current similar to that observed with Hm1a Bertelli et al, 2019;Cestele et al, 2013a;Cestele et al, 2008;Cestele et al, 2013b;Fan et al, 2016;Mantegazza and Broccoli, 2019;Mantegazza and Cestele, 2017). Notably, it has been recently reported that Hm1a rescued the hypoexcitability of hippocampal GABAergic neurons and the severity of the epileptic phenotype in epileptic Scn1a +/knock-out mice, but it did not modify firing properties of wild type hippocampal GABAergic neurons in brain slices (Richards et al, 2018).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Another folding/trafficking defective FHM mutation, Na v 1.1-L1670W, showed that functional effect can be switched from a complete loss of function to the gain of function by expression in neurons 47 . Epileptogenic mutations cause a variable degree of loss of function, whereas FHM mutations can, in some cases of functional studies, appear as loss of function because of rescuable folding/trafficking defects; other studies, however, confirmed that FHM mutations cause a gain of function of Na v 1.1 48,49 . Several studies have also suggested that environmental factors and genetic modifiers may influence the clinical phenotype of SCN1A-related epilepsy [41][42][43][44][45]50,51 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, when this mutation was studied in the cardiac Na V 1.5 channel, it did not cause folding defects and induced mild modifications of functional properties that are consistent with moderate gain‐of‐function . Other reports have now confirmed that FHM mutations cause gain‐of‐function of Na V 1.1 . One of these reports identified another folding/trafficking defective FHM mutation for which the rescue induced by expression in neurons switched the functional effect from complete loss‐of‐function to large gain‐of‐function because of the modifications of gating properties .…”
Section: Functional Effects On Channel/neuronal Excitability Propertimentioning
confidence: 92%